Pengaruh Likuiditas dan Solvabilitas terhadap Kinerja Keuangan dengan Good Corporate Governance sebagai Variabel Moderasi : (Studi Kasus pada Perusahaan Sektor Transportasi dan Logistik yang Terdaftar di BEI Periode 2020-2022) - Dinda Putri Septiani; Hariyati Hariyati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of this study is to examine the effect of liquidity and solvency on financial performance with good corporate governance as a moderating variable. This study uses a quantitative methodology using purposive sampling techniques to collect data from 28 transportation and logistics companies that were listed on the Indonesia Stock Exchange (BEI) between 2020 and 2022. Multiple linear regression techniques were used in this study using SPSS 26 software. The study’s findings reveal that liquidity has a significant effect on financial performance, but solvency has no effect. GCG is able to moderate the influence of liquidity on financial performance, but is unable to do the same for solvency.